Fed-batch fermentation of lactobacillus plantarum: a modelling and simulation (M&S) approach for biomass production - Hasan, Muhammad Faheem (2016)
Nowadays, fed-batch fermentation is developed in many areas such as industrial, cosmetics, health care body, supplement and many more. It increases as enhance the number of the fermentation process. Previous researchers showed that fed-batch fermentation able to increase the biomass yield of many strains. Improvements the biomass yield are interested because biomass from lactic acid bacteria (LAB) fermentation such as Lactobacillus plantarum is widely used in food and pharmaceutical industry. The purposes of this research are to study the ability and feasibility of fed-batch fermentation to improve biomass production of L. plantarum. Monod model used to describe the substrate limitation of L. plantarum and the product inhibition of L. plantarum follows the non-competitive model. Besides, the lactic acid production follows Luedeking and Piret model. Then, the model is applied to stimulate the fermentation of fed-batch by using computational tools, MATLAB® Software. From the results of the simulation, fed-batch fermentation of Lactobacillus plantarum showed that substrate limitation and substrate inhibition could be avoided. Besides that, the exponential fed-batch fermentation also revealed that product inhibition could be eliminated by added fresh feed diluting the product concentration. However, fed batch fermentation was found not economically feasible because a significant amount of substrate is needed to minimise the product inhibition effect. Therefore, fed-batch fermentation plays more importance role if the fermentation strains have high Ks value or level Kp value.